2013
DOI: 10.3109/03014460.2012.759621
|View full text |Cite
|
Sign up to set email alerts
|

Implications of market integration for cardiovascular and metabolic health among an indigenous Amazonian Ecuadorian population

Abstract: Background: Market integration (MI), the suite of social and cultural changes that occur with economic development, has been associated with negative health outcomes such as cardiovascular disease; however, key questions remain about how this transition manifests at the local level. Aim: The present paper investigates the effects of MI on health among Shuar, an indigenous lowland Ecuadorian population, with the goal of better understanding the mechanisms responsible for this health transition. Conclusions: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
122
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 72 publications
(135 citation statements)
references
References 46 publications
12
122
0
1
Order By: Relevance
“…They are a natural fertility population and traditionally lived in scattered matrilocal household clusters in traditional thatch-wall, earthen-floor houses (Karsten, 1935; Descola, 1996; Rubenstein, 2001), although plank houses with tin roofs are becoming more common. Present day subsistence remains based on horticulture, fishing, hunting and gathering, yet they are currently experiencing increasingly rapid infrastructure development and market integration as a result of regional economic development (Blackwell et al, 2009; Liebert et al, 2013). However the villages in the present study subsist with limited daily access to markets or exposure to economic development.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are a natural fertility population and traditionally lived in scattered matrilocal household clusters in traditional thatch-wall, earthen-floor houses (Karsten, 1935; Descola, 1996; Rubenstein, 2001), although plank houses with tin roofs are becoming more common. Present day subsistence remains based on horticulture, fishing, hunting and gathering, yet they are currently experiencing increasingly rapid infrastructure development and market integration as a result of regional economic development (Blackwell et al, 2009; Liebert et al, 2013). However the villages in the present study subsist with limited daily access to markets or exposure to economic development.…”
Section: Methodsmentioning
confidence: 99%
“…Further, Cepon-Robins et al (2013) reported that 65% of the population in this particular region is infected with parasitic worms, with even higher prevalence among children. Stunting among children is a common public health concern, and is relevant to ongoing studies investigating metabolic health in the context of economic transitioning populations (Santos & Coimbra, 2003; Foster et al, 2005; Orellana et al, 2009; Blackwell et al, 2009; Liebert et al, 2013) making nutrition-related health research a high priority in this region.…”
Section: Methodsmentioning
confidence: 99%
“…The Shuar are a large indigenous population of 40,000-110,000 individuals inhabiting the neotropical Amazonas region of southeastern Ecuador. Traditionally subsistence forager-horticulturalists, recent development of infrastructure in some regions of Shuar territory has resulted in increased contact with outsiders and varying degrees of integration into the wider market economy (Liebert et al, 2013;Lu, 2007). Many communities now possess schools, electricity, running water, and other modern features.…”
Section: Study Populationmentioning
confidence: 99%
“…Many communities now possess schools, electricity, running water, and other modern features. Despite these changes, however, diet among the Shuar remains generally poor and group members, particularly children, continue to face a heavy burden of infectious disease (Blackwell et al, 2010;Cepon-Robins et al, 2014;Liebert et al, 2013). Physical growth at the population level is characterized by rates of childhood stunting of 40% but low incidence of underweight and wasting, a pattern typical of other indigenous Amazonians (Blackwell et al, 2009;Urlacher et al, 2016).…”
Section: Study Populationmentioning
confidence: 99%
“…The combination of rural, agrarian lifeways and increasing market integration produces a distinct economic and nutritional landscape shared across many Latin American populations (Rivera et al, 2004). Compared to local indigenous groups, such as the Shuar however, Colonos are experiencing a later stage of this economic and nutrition transition (Liebert et al, 2013). …”
Section: Participant Population and Hypothesesmentioning
confidence: 99%